The political role of 'cultural entrepreneurs' in Kenya: Claiming recognition through the memorialisation of Koitalel Samoei and Nandi heritage. Issue 2 (3rd April 2018) - Josse-Durand, Chloé
ABSTRACT: Since 2010, negotiations surrounding the political interpretation of the past in Kenya are taking place within a new constitutional framework. With the implementation of devolution supposed to be at the core of democratisation, socioeconomic and political claims at a county level are increasingly taking shape on an ethno-cultural basis, nurtured by communities' long-term constructions of memory. Under the guise of preserving and promoting cultural heritage, this article argues that the contemporary emergence of community museums in Kenya illustrates the growing salience of ethnic identities in the political sphere, used as a resource and a category of action both by the state and cultural entrepreneurs. By occupying an intermediary position in negotiations and public decision-making and using a new kind of capital – cultural heritage and its conservation – the latter strengthen their position both as 'entrepreneurs of themselves' and 'entrepreneurs of a collective memory' or 'we-entrepreneurs', here understood as a set of representations of the past shared by a social group. The article will discuss not only what politics do to museums but also how museums impact on political dynamics, drawing on research that centred on a case study of an ethnographic community museum and a mausoleum dedicated to Nandi culture and the 'hero' Koitalel Samoei in the Northern Rift Valley. By focusing on the role played by these new cultural actors in the (re)writing of local history, this article explores the use of cultural heritage in the reconfiguration of political competition and the making of land claims at a grassroots level in contemporary Kenya.